2022
DOI: 10.1063/5.0103367
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking induced bandgap opening in epitaxial germanene on WSe2

Abstract: Germanene has attracted much attention because the material was predicted to host Dirac fermions. However, the synthesis of germanene is still in its infancy; moreover, the predicted tiny bandgap induced by the spin–orbit coupling is far from practical applications for nanoelectronic devices. Herein, quasi-freestanding germanene with linear dispersion relation of the band structure is well grown on a WSe2/Au(100) substrate. Band structure calculations reveal that the interaction of germanene with the substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In the present study, we have singled out the additional versatility of germanene monolayers and related interfaces 87 , whose multiple light-matter modes are strongly dependent on both geometry and charge carrier concentration. We remark that the latter is a novel feature, which marginally involve other 2DDMs, and as such it requires an improved analysis, in line with what has been reported here, for a correct tuning of the input parameters of possible germanene-based devices.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have singled out the additional versatility of germanene monolayers and related interfaces 87 , whose multiple light-matter modes are strongly dependent on both geometry and charge carrier concentration. We remark that the latter is a novel feature, which marginally involve other 2DDMs, and as such it requires an improved analysis, in line with what has been reported here, for a correct tuning of the input parameters of possible germanene-based devices.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have singled out the additional versatility of germanene monolayers and related interfaces 87 , whose multiple light-matter modes are strongly dependent on both geometry and charge carrier concentration. We remark that the latter is a novel feature, which marginally involve other 2DDMs, and as such it requires an improved analysis, in line with what has been reported here, for a correct tuning of the input parameters of possible germanenebased devices.…”
Section: Discussionmentioning
confidence: 99%
“…Hoat et al 17 proposed an effective approach to manually creating the band gap of Ge by chemical functionalization and doping of Ge with halogen atoms. Wu et al 18 demonstrated that a sizable band gap in Ge can be opened by controlling the interaction between Ge and the substrate both experimentally and theoretically. Ge more easily opens the Dirac cone band gap than graphene, which can bring more special physical properties.…”
Section: Introductionmentioning
confidence: 99%